Thermodynamic and kinematic structure of tropical cyclones in the western North Pacific based on ACARS/AMDAR - Ito, Kosuke; Yamamoto, Ren (Frontiers in Earth Science, 2022)
Meteorological variables are often reported by commercial aircraft flying around tropical cyclones (TCs). They are archived in Aircraft Communications, Addressing, and Reporting System/Aircraft Meteorological Data Relay (ACARS/AMDAR). Therefore, they are potentially useful for constructing a composite mean structure of TCs based on in-situ measurements. The number of temperature and wind observations are 4.0 × 106 and 1.0 × 104 within the radius of 1,200 km and 100 km from the TC center during 2010–2020, respectively. The warm-core potential temperature anomaly with respect to the climatology is 6.4 K, 9.1 K, and 14.4 K maximized around 300 hPa for weak, moderate, and strong TCs, respectively. The composite of the potential temperature anomaly potentially extends more than 1,000 km from the TC center in the upper troposphere, cautioning the typical definition of the environment. The region of significant upper-level positive potential temperature anomalies extends broadly with increasing TC intensity. Moreover, large TCs tend to have a broad and deep upper-level warm core for a given intensity. In addition, we ensured that a single observation of potential temperature around 300 hPa could be used as a proxy for minimum sea level pressure. Low-level inflow and upper-level outflow were detected in the ACARS/AMDAR data.